2006
DOI: 10.1007/s00268-005-0462-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Number and Extent of Positive Lymph Nodes in 200 Patients with Thoracic Esophageal Squamous Cell Carcinoma after Three‐field Lymph Node Dissection

Abstract: Together, number and extent of positive lymph nodes can be considered an independent predictor of a high risk of recurrence. Although cervical lymphatic spreading was risk factor for worse survival, patients with upper tumors may have survival benefit after cervical lymph node dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 22 publications
6
79
2
1
Order By: Relevance
“…The efficacy of three-field lymphadenectomy for improving the survival of patients with esophageal cancer has also been demonstrated by Lerut et al [24] and Altorki et al [25]. Many Japanese studies have subsequently reported a benefit of three-field lymphadenectomy [26,27,28,29]. …”
Section: Esophageal Resectionmentioning
confidence: 82%
“…The efficacy of three-field lymphadenectomy for improving the survival of patients with esophageal cancer has also been demonstrated by Lerut et al [24] and Altorki et al [25]. Many Japanese studies have subsequently reported a benefit of three-field lymphadenectomy [26,27,28,29]. …”
Section: Esophageal Resectionmentioning
confidence: 82%
“…Lymph nodes metastases to the neck, chest, and abdomen have been detected frequently in resected specimens from patients with thoracic esophageal squamous cell carcinoma (ESCC) (1). Thus, subtotal esophagectomy plus three-field lymph node dissection (cervical, thoracic and abdominal) has been introduced as an effective therapeutic strategy for the treatment of localized thoracic ESCC in Japan (2,3). However, due to high morbidity and mortality rates following thoracotomy and laparotomy for patients with thoracic ESCCs, the use of surgery to treat this condition has been limited (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…1) Despite advances in surgical treatment, surgery alone has not improved the prognosis of patients with T4 esophageal tumors. [2][3][4] Furthermore, the combination of resection of neighboring organs with esophagectomy has not improved survival despite the high incidence of morbidity and mortality. 4,5) On the other hand, palliative resection (R1 or R2) followed by radiotherapy with or without chemotherapy has also failed to improve survival compared with nonsurgical treatment.…”
Section: Introductionmentioning
confidence: 99%